Efeitos da migração sobre a fecundidade: um estudo comparativo entre mulheres nordestinas imigrantes em São Paulo, mulheres não-migrantes naturais do estado e mulheres não-migrantes naturais do Nordeste - Bruna Atayde Signorini (2017)
This dissertation compared the differences in fertility amongst groups of women with distinct migration status by using two different matching methods: the Propensity Score Matching (PSM) and the Coarsened Exact Matching (CEM). The current fertility was represented by the probability of having an alive born child in the 12 months prior to the reference date of the Brazilian Demographic Census of 2010. Immigrant women born in the Northeast region of Brazil but living in the state of São Paulo, non-migrant women born and living in São Paulo and non-migrant women born and living in the states of the Northeast region during the census date were selected in order to control the migration context differences as much as possible. The final matching results obtained by the use of the CEM method showed evidences of disruption of fertility due to migration and evidences of fertility behavior assimilation of the destiny place by the northeastern immigrant women with a larger time of residence in São Paulo. The comparison between the matching methods showed the advantages of the Coarsened Exact Matching relatively to Propensity Score Matching. That was due specially to the operational simplicity of the CEM, which was crucial for obtaining the results with all the necessary variables.